Implementation of the Silungkang Songket Development Program with Natural Dyeing by the Koperindag Department in Sawahlunto City - Nazirwan, Nazirwan; Tovalini, Krismena; Andini, Surya (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
The aim of the research is to find out an overview of the implementation of the Silungkang songket development program with natural dyeing by the Koperindag Department in Sawahlunto City. The importance of implementation is to understand the implementation of the Silungkang songket development program policy with natural dyeing by the Cooperative Industry and Trade Service in Sawahlunto City, namely the synergy between UKM actors and the Sawahlunto City Government, which acts as a regulator and facilitator in empowering songket craftsmen so that they are able to increase the ability of Silungkang songket craftsmen with natural dyeing. The research method uses a qualitative-descriptive approach, with the type of data collection carried out through interviews with the Head of the Sawahlunto City Cooperative Industry and Trade Service, the Head of the Sawahlunto City Bappeda, the Sawahlunto City Cooperative Industry and Trade Head, Sawahlunto City IKM TPL, Silungkang songket craftsmen with natural dyeing, and the community around the central area. The research results show why the implementation of the Silungkang Songket Development Program with Natural Dyeing by the Koperindag Department in Sawahlunto City has not been optimal due to the lack of clarity in the SOP, limited human resources, inadequate supporting facilities and infrastructure, access to capital sources that is still limited, the absence of UPT and third parties for business development, and socialization and coordination that are not yet massive.